Role of cytokinins in the regulation the chilling stress response in Triticum aestivum and Triticum spelta - Voytenko, L.V.; Shcherbatiuk, M.M.; Vasyuk, V.A.; Kosakivska, I.V. (Доповіді НАН України, 2024)
The research is devoted to the study of the eff ect of chilling (+4 °C, 2 h) on cytokinin homeostasis in 14-day stressed and 21-day restored plants of winter wheat (Triticum aestivum L.) cv. “Podolyanka” and spelt wheat (Triticum spelta L.) cv. “Frankenkorn”. Our study revealed that chilling induces complex changes in the content and distribution of cytokinins in plants that are species- and organ-specifi c. Aft er chilling, the total cytokinin content in the roots of winter wheat cv. “Podolyanka” increased threefold due to the accumulation of trans-zeatin-O-glucoside, trans-zeatin, isopentenyladenine and isopentenyladenosine. Stress did not aff ect trans-zeatin riboside accumulation in roots but induced a fourfold increase in its content in the shoots of winter wheat cv. “Podolyanka”. Th e total content of cytokinin in the roots of spelt wheat cv. “Frankenkorn” decreased by 1.4 times due to decline in trans-zeatin-O-glucoside and trans-zeatin riboside content, while in shoots, it decreased by 1.2 times owing to reduced trans-zeatin-O-glucoside and isopentenyladenine levels. Prolonged exposure to chilling was manifested by an increase in hormone levels in both 21-day-old species. Our data revealed common and distinct traits in cytokinin homeostasis between winter wheat cv. “Podolyanka” and spelt wheat cv. “Frankenkorn” during rapid adaptation and the recovery period, providing new insights into the response of these species to chilling.